Violence against Women: Notifications of Health Professionals in Rio Grande do Sul - Lawrenz,Priscila (2018)
Abstract The aim of this study was to characterize the situations of violence against women reported by health professionals in Rio Grande do Sul. A total of 20.999 reports were performed between 2010 and 2014. The most frequent reports included women aged 19 to 29 years old. The most frequent type of violence was physical, and the victim’s residence was the most frequent place. Most of perpetrators were male, partner or ex-partner of the victim. Women were referred more frequently to clinics and police station. The results can support strategies for prevention and coping violence against women. The study allowed identifying weaknesses in the report information, as well as in the referrals made, indicating the need for investments in the training of health professionals.